2018
DOI: 10.3390/nu10020192
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Carbohydrates, in Isolation and Combined with Caffeine, on Cognitive Performance and Mood—Current Evidence and Future Directions

Abstract: This review examines the effects of carbohydrates, delivered individually and in combination with caffeine, on a range of cognitive domains and subjective mood. There is evidence for beneficial effects of glucose at a dose of 25 g on episodic memory, but exploration of dose effects has not been systematic and the effects on other cognitive domains is not known. Factors contributing to the differential sensitivity to glucose facilitation include age, task difficulty/demand, task domain, and glucoregulatory cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 215 publications
(363 reference statements)
0
10
0
Order By: Relevance
“…Considering that no beneficial effects of CHOs on mood were identified, our metaanalysis calls into question the existence of a mood-boosting mechanism (serotonin-based or otherwise) related to CHO consumption. In fact, the validity of the CHO-serotonin mechanism and, by extension, the CHO-mood relationship has received criticism and has been difficult to replicate in experimental settings (for reviews, see Benton, 2002;Boyle et al, 2018;van de Rest et al, 2017). Interestingly, even in studies that have found CHO to influence serotoninergic activity, it is suggested that this effect is observable only under specific conditions (e.g., stress; Markus, 2007), and for clinical populations rather than healthy individuals (for a review, see Wurtman and Wurtman, 2018), calling into question the validity of the CHO-mood relationship for the general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that no beneficial effects of CHOs on mood were identified, our metaanalysis calls into question the existence of a mood-boosting mechanism (serotonin-based or otherwise) related to CHO consumption. In fact, the validity of the CHO-serotonin mechanism and, by extension, the CHO-mood relationship has received criticism and has been difficult to replicate in experimental settings (for reviews, see Benton, 2002;Boyle et al, 2018;van de Rest et al, 2017). Interestingly, even in studies that have found CHO to influence serotoninergic activity, it is suggested that this effect is observable only under specific conditions (e.g., stress; Markus, 2007), and for clinical populations rather than healthy individuals (for a review, see Wurtman and Wurtman, 2018), calling into question the validity of the CHO-mood relationship for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, an increasing number of empirical reports have suggested that ingestion of CHOs does not lead to any pronounced increases in subjective mood and overall affect, but can even have detrimental effects on mood (Adan and Serra-Grabulosa, 2010; Brody and Wolitzky, 1983;Duckworth et al, 2013;Giles et al, 2012;Harte and Kanarek, 2004;Howard and Marczinski, 2010;Jones and Sünram-Lea, 2008;Meikle et al, 2004;Miller et al, 2013Miller et al, , 2014O'Neal et al, 2013;Owen et al, 2013;Qin et al, 2017;Hammersley, 1998, 1995;Riby et al, 2004;Scholey et al, , 2009Scholey and Fowles, 2002;Scholey and Kennedy, 2004;Seo et al, 2014;Stollery and Christian, 2013;Sünram-Lea et al, 2011;Ullrich et al, 2015;van der Zwaluw et al, 2014;Zacchia et al, 1991). Researchers have acknowledged the complicated nature of the results and have challenged the reliability of CHO effects on mood (Benton, 2002;Boyle et al, 2018;van de Rest et al, 2017). Whereas CHO effects on cognition are strong and well-documented (Messier, 2004;Riby, 2004;Smith et al, 2011), the effects of CHO administration on mood are not as dependable, a finding that could be attributed to a number of factors including the diverse methodologies employed by researchers to assess CHO-mood interactions.…”
Section: Carbohydrates and Mood: Mechanisms And Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…11 It suggests that there is some association between the cognition-regulatory effects of caffeine and glucose when used in unison. 12 Some energy drinks also contain Amphetamine which causes elevation of mood & euphoria. 5 High doses of Amphetamine can lead to delusions & simulate schizophrenia-like conditions.…”
Section: Introductionmentioning
confidence: 99%